An LQR-Based ANFIS Control for Double-Linked Inverted Pendulum on Cart - Pham, Truong-Phuong-Nam; Tran, Trong-Bang; Nguyen, Van-Dong-Hai; Nguyen, Tai-Tue; Nguyen, Gia-Thinh; Nguyen, Duy-Phat; Nguyen, Dong-Khang; Ha, Van-An; Trinh, The-Nam-Chau; Nguyen, Trung-Thang (Journal of Fuzzy Systems and Control, 2025)
This paper presents a double-linked inverted pendulum on a cart system, which is highly nonlinear and inherently unstable. In the simulation, the state variable outputs are processed through three ENCODER blocks with a resolution of 1000 pulses, as we aim to develop a mathematical model that closely approximates real-world experiments. The objective of this study is to use an ANFIS controller to learn from data that closely resembles the actual system behavior under an LQR controller and apply it in a simulation environment to evaluate the stability and response of the system under both ANFIS and LQR controllers. The results show that the ANFIS controller provides better responses than the LQR controller.